2021
DOI: 10.3390/polym13030326
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive and Conductive Chitosan-Polyurethane Biocompatible Thin Films with Potential Coating Application

Abstract: Conductive thin films have great potential for application in the biomedical field. Herein, we designed thermoresponsive and conductive thin films with hydrophilicity, strain sensing, and biocompatibility. The crosslinked dense thin films were synthesized and prepared through a Schiff base reaction and ionic interaction from dialdehyde polyurethane, N-carboxyethyl chitosan, and double-bonded chitosan grafted polypyrrole. The thin films were air-dried under room temperature. These thin films showed hydrophilici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Processing into a freestanding thin film is the easiest choice and affordable route to evaluate the physico-mechanical properties and biocompatibility of the designed nanocomposites. [42][43][44] Chitosan nanocomposite thin films can be fabricated using solution casting, melt mixing, and in-situ nanoparticle synthesis approaches. Solution casting is usually carried out using water, cell culture medium, and sometimes organic solvents.…”
Section: Chitosan-based Nanocomposite Scaffolds For Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Processing into a freestanding thin film is the easiest choice and affordable route to evaluate the physico-mechanical properties and biocompatibility of the designed nanocomposites. [42][43][44] Chitosan nanocomposite thin films can be fabricated using solution casting, melt mixing, and in-situ nanoparticle synthesis approaches. Solution casting is usually carried out using water, cell culture medium, and sometimes organic solvents.…”
Section: Chitosan-based Nanocomposite Scaffolds For Tissue Engineeringmentioning
confidence: 99%
“…Various existing methodologies have been adapted for processing of chitosan‐based nanocomposites into films, 34 fiber‐meshes, 35 hydrogels, 36–40 and 3D printed constructs 41 to mimic the 3D environment of tissues. Processing into a freestanding thin film is the easiest choice and affordable route to evaluate the physico‐mechanical properties and biocompatibility of the designed nanocomposites 42–44 . Chitosan nanocomposite thin films can be fabricated using solution casting, melt mixing, and in‐situ nanoparticle synthesis approaches.…”
Section: Chitosan‐based Nanocomposite Scaffolds For Tissue Engineeringmentioning
confidence: 99%
“…A conventional overlay coating method was initially attempted to decorate AdSP on the substrate dish, which was conducted by overlay coating and washing three times, followed by drying [ 33 ]. The outcome showed that a significant difference between the dish treated by the overlay coating method and the untreated non-adhesive dish did not exist, indicating that AdSP was not readily attached to the substrate by the regular casting.…”
Section: Resultsmentioning
confidence: 99%
“…AdSP was coated on the material surface based on a self-developed method inspired from the previous literature [ 33 ]. The surface of non-adherent polystyrene dish (diameter/height: 35/10 mm, Greiner Bio-One, Frickenhausen, Germany) was used as the pristine substrate.…”
Section: Methodsmentioning
confidence: 99%
“…Polyurethane is another polymer that can be engineered to manifest reversible changes in chemical and physical characteristics upon exposure to temperature variations. [87][88][89] One example of polyurethane used as a thermo-responsive coating material for CRF application is the study by Qiao et al, who employed polycaprolactone (PCL) with varying molecular weights (PCL500, PCL1000, PCL2000, and PCL3000) as raw materials to produce six types of polyurethane-based CRF coatings by reacting polyether polyol (PPG)/PCL blends with methylene diphenyl diisocyanate (MDI). Results demonstrated that PPG/PCL2000-based PUCF blends can copolymerize with MDI to generate a block copolymer with a two-phase structure (crystalline/amorphous).…”
Section: Thermo-responsive Hydrogelsmentioning
confidence: 99%